A Delphi consensus of Mindfulness Based Cognitive Therapy for managing anxiety and blood pressure in hypertensive patient protocol - AM, Ady Irawan.; Janmabhumi, Anjani; Wulandari, Ziara Arum; Santoso, Aris Prio Agus; Putri, Anggie Pradana (Alta Dharma Publisher, 2023)
Hypertension not only stands as a primary contributor to cardiovascular diseases but also exhibits a strong interconnectedness with psychological aspects, one of which is anxiety. This study aims to develop a consensus-based protocol for the implementation of Mindfulness-Based Cognitive Therapy (MBCT) in managing anxiety and blood pressure among hypertensive patients. We conducted a Delphi consensus study included a panel of experts with diverse background in hypertension, mindfulness, and psychology. Eleven experts participated in the three rounds of Delphi consensus. The Delphi consensus process resulted in a robust and widely accepted protocol that integrates mindfulness technique, cognitive restructuring, and lifestyle modifications. The definition, aims, indication, and procedures. The core of MBCT covering introduction of mindfulness, mindful awareness of though and emotions, mindful eating and hypertension with D.A.S.H., cultivating gratitude and positivity, mindfulness in daily activities, mindfulness for coping with anxiety, mindfulness and self-compassion, and review and integration. The study represents a crucial step in bridging the gap between research and clinical also community nursing practice, providing a structures framework for healthcare professionals to address anxiety and hypertension simultaneously. This consensus holds significant clinical and community promise, offering a standardized approach to MBCT implementation in hypertensive patient care. By addressing both psychological and physiological aspects, it has the potential to reduce anxiety levels and contribute to improved blood pressure control.